PEMBELAJARAN MENULIS PUISI DENGAN PENDEKATAN KONTEKSTUAL - Neneng Ulfatul Hasanah; Ika Mustika; Restu Bias Primandhika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Learning to write poetry is generally considered a difficult thing for students to do. This difficulty is due to the lack of or low vocabulary of students in writing poetry, so that when writing poetry, many students have difficulty expressing ideas and completing their writing into a written poem. This research was conducted at SMA PLUS AR-RAUDHAH with 24 students as research subjects. The formulation of the problem faced in this study is how difficult are students in writing poetry? This study aims to answer the formulation of problems regarding students' difficulties in writing poetry, as well as to determine an increase in the initial and final test scores in learning to write poetry. This research method uses descriptive qualitative and uses data collection techniques in the form of skills tests. Based on the results of research during learning activities, it shows that writing poetry using a contextual approach has been effective for use in classroom learning by getting an average score on the initial test 58.3 and the final test score with an average score of 76.8. Thus the use of a contextual approach to learning to write poetry is effective for use in classroom learning which is able to experience an increase in student learning outcomes by obtaining a score above the KKM average in Indonesian subjects.